A Looking Glass War: Bangladesh’s Pendulum-swing Liberation War Cinema - Mohaiemen, Naeem (BioScope South Asian screen studies, 2025)
The 1971 war that imploded Pakistan’s ‘two-wing’ geography and created Bangladesh out of the former East Pakistan wing is a foundational event within Bangladesh’s national narrative. Anniversaries, monuments and cultural productions codify the war’s milestones and protagonists. South Asian cinema has attempted a ‘national imagination’ in various forms since 1947 – sometimes loyal to boundaries created by partition, at other times trying to create subnational (e.g., ‘Bengali’ within ‘Indian’) identities. Bangladeshi cinema has also attempted to build up a national identity through an initial centring, a later decentring and then a return to narratives around the 1971 Liberation War as the singular event that created the basis for territorial Bangladesh. It has done this by erasing both 1947 partition trauma, and the experiences of the East Pakistan years (1948–1970), as a subject for cinema. Against this backdrop, I propose reading two Bangladeshi theatrical films, made 40 years apart, to signpost some narrative foci shifts regarding religion as a proxy for political alliance, and women’s besieged honour within the war. The two films I discuss are Ora Egaro Jon/They Are Eleven (Islam, 1972, Ora Egaro Jon (They Are Eleven) [Film]), completed a year after the war, and Meherjaan (Hossain, 2011, Meherjaan [Film]), released in the 40th year of Bangladesh’s independence. These two films illustrate a shift in religiosity as a suspect element and the reification of women’s role as one of unwilling body sacrifice. This points to the unsettled fluidity of a Bangladeshi identity formed through war, despite the state, civil society and cultural production efforts to inscribe the idea of an inevitable teleology and narrative closure in postwar identity.